Sosial Security Administering Body (BPJS) Services and Utilities – Scope Review for Patients Privacy Concern in Sibolga City - Situmorang, Benri; Sansuwito, Tukimin Bin; Dioso, Regidor III; Herlina (International Journal of Natural and Health Sciences, 2024)
For the convenience of BPJS users and the general public, participants can access the Health Insurance Nationally (JKN) Mobile Program from any location. It is a digital version of the BPJS business concept, at any time, and without time constraints. The convenience involves knowing participant family information, updating membership data, and paying BPJS fees. This research aims to determine how implementing National Insurance Healthy (JKN) can improve BPJS health services in Sibolga. This kind of study uses a qualitative approach and is descriptive. Four sources were used in this study. Meanwhile, methods for gathering data include recordkeeping, interviewing, and observation. The study's findings demonstrate that BPJS health services in Sibolga are effective and efficient thanks to National Insurance Healthy (JKN) Mobile Program, which greatly facilitates the administrative tasks carried out by the BPJS health office in providing care for the local population. Because of its various capabilities, Getting BPJS health services is easier via the JKN Mobile Program. Participants can obtain BPJS health services quickly by utilizing the JKN Mobile Program or care center, negating their need to visit the BPJS health office